Structural Imaging Changes and Behavioral Correlates in Patients with Crohn’s Disease in Remission - Nair, Veena A.; Beniwal-Patel, Poonam; Mbah, Ifeanyi; Young, Brittany M.; Prabhakaran, Vivek; Saha, Sumona (Frontiers in Human Neuroscience, 2016)
BACKGROUND: Crohn’s disease (CD) is a subtype of inflammatory bowel disease (IBD) caused by immune-mediated inflammation in the gastrointestinal tract. The extent of morphologic brain alterations and their associated cognitive and affective impairments remain poorly characterized. AIMS: We used magnetic resonance imaging (MRI) to identify structural brain differences between patients with Crohn’s disease in remission compared to age-matched healthy controls and evaluated for structural-behavioral correlates. METHODS: 20 patients and 20 healthy, age-matched controls were recruited in the study. Group differences in brain morphometric measures and correlations between brain measures and performance on a cognitive task, the verbal fluency task, were examined. Correlations between brain measures and cognitive measures as well as self-reported measures of depression, personality, and affective scales were examined. RESULTS: Patients showed significant cortical thickening in the left superior frontal region compared to controls. Significant group differences were observed in sub-cortical volume measures in both hemispheres. Investigation of brain-behavior correlations revealed significant group differences in the correlation between cortical surface area and verbal fluency performance, although behavioral performance was equivalent between the two groups. The left middle temporal surface area was a significant predictor of verbal fluency performance with controls showing a significant positive correlation between these measures, and patients showing the opposite effect. CONCLUSIONS: Our results indicate key differences in structural brain measures in patients with CD compared to controls. Additionally, correlation between brain measures and behavioral responses suggest there may be a neural basis to the alterations in patients’ cognitive and affective responses.